2015
DOI: 10.4103/0970-9290.167645
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of hydroxyapatite and nano-bioglass in two forms of conventional micro- and nano-particles in repairing bone defects (an animal study)

Abstract: Nano-HA and nano-bioglass biomaterials showed promising results when compared to conventional micro-particles in the repair of bone defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…As reported in the study HA et al (2015), nanoHA-induced cellular regulation in osteoblast did not occur in cells cultured with nanosized silica [ 138 ]. This is also in line with in vivo findings; after 15 days of implantation, nanoHA was superior to nano-bioglass, causing the highest bone formation rate [ 139 ]. Thus, we indicated that the cellular response induced by nanoHA was due to the material property of nanoHA.…”
Section: Other Cellular Events Induced By Hasupporting
confidence: 88%
“…As reported in the study HA et al (2015), nanoHA-induced cellular regulation in osteoblast did not occur in cells cultured with nanosized silica [ 138 ]. This is also in line with in vivo findings; after 15 days of implantation, nanoHA was superior to nano-bioglass, causing the highest bone formation rate [ 139 ]. Thus, we indicated that the cellular response induced by nanoHA was due to the material property of nanoHA.…”
Section: Other Cellular Events Induced By Hasupporting
confidence: 88%
“…Biomaterials fabricated into nanoscale (1-100 nm) structures (nanomaterials) have been shown to mimic the native ECM and promote cell adhesion and osteogenic differentiation. [20][21][22] Graphene-based nanomaterials have recently been recognized as useful components of bone tissue engineering scaffolds. Graphene derivatives are preferred over the pristine form and can be produced relatively easily by functionalization of pristine graphene, with the ultimate goal of reducing pristine graphene's toxicity and increasing its usability in biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Both support the attachment and proliferation of bone‐forming osteoblast cells and assist the formation of mineralized bone matrix 23,24 and have been used in various FDA‐approved medical devices since 1985 25,26 . Several studies suggest BG superiority over HA because of the following reasons 27–29 : (1) The faster proliferation of osteoblasts and bone formation; (2) Better adhesion and bonding to surrounding soft tissues elements e.g., collagen without induction of fibrous capsule in vivo; (3) Higher bioactivity due to ion release and rich silica layer; (4) Anti‐microbial properties; (5) Finally bioglass' degradation products could induce the growth factors production and cell proliferation. They could also trigger the gene expression of osteoblasts 30 …”
Section: Introductionmentioning
confidence: 99%
“…21,22 Both support the attachment and proliferation of bone-forming osteoblast cells and assist the formation of mineralized bone matrix 23,24 and have been used in various FDA-approved medical devices since 1985. 25,26 Several studies suggest BG superiority over HA because of the following reasons [27][28][29] : (1) The faster proliferation of osteoblasts and bone formation; (2) Better adhesion and bonding to surrounding soft tissues elements e.g., collagen without induction of fibrous capsule in vivo;…”
mentioning
confidence: 99%